Hegemony Da'wah Of Nahdlatul Ulama Kiai In The 2020 Regent Election: A Case Study In Semarang District - Muhyiddin, Ahmad Shofi (Universitas Islam Negeri Raden Intan Lampung, 2023)
Kiai as a religious elite have a high